2023
DOI: 10.1186/s40795-023-00709-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron fortification on anaemia and risk of malaria among Ghanaian pre-school children with haemoglobinopathies and different ABO blood groups

Abstract: Background Haemoglobinopathies such as sickle cell disorder and glucose-6-phosphate dehydrogenase (G6PD) deficiency as well as differences in ABO blood groups have been shown to influence the risk of malaria and/or anaemia in malaria-endemic areas. This study assessed the effect of adding MNP containing iron to home-made weaning meals on anaemia and the risk of malaria in Ghanaian pre-school children with haemoglobinopathies and different ABO blood groups. Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In the present study, we found that women were the majority (68.6%), and in all groups, they constituted the majority, except for the ARh(-) group and 75% of the SS individuals found in the study were women, although there was no statistical difference between gender and blood groups, the study showed a relationship between sickle cell trait and gender (p < 0.05). Data from the present study seem to be similar to the study carried out in Ghana with children, where the authors found that blood group O was dominant (41.4%), followed by blood group A (29.6%) and group B blood group (23.3%), while AB blood group (5.7%) had the lowest frequency in the study, however, the prevalence of G6PD de ciency in hemizygous men (8.5%) was signi cantly higher than in homozygous women (2.7%) (p < 0.05) and the prevalence rates of sickle cell trait (HbAS and HbSC) and sickle cell disease (HbSS) were 17.5% and 0.5%, respectively [25].…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, we found that women were the majority (68.6%), and in all groups, they constituted the majority, except for the ARh(-) group and 75% of the SS individuals found in the study were women, although there was no statistical difference between gender and blood groups, the study showed a relationship between sickle cell trait and gender (p < 0.05). Data from the present study seem to be similar to the study carried out in Ghana with children, where the authors found that blood group O was dominant (41.4%), followed by blood group A (29.6%) and group B blood group (23.3%), while AB blood group (5.7%) had the lowest frequency in the study, however, the prevalence of G6PD de ciency in hemizygous men (8.5%) was signi cantly higher than in homozygous women (2.7%) (p < 0.05) and the prevalence rates of sickle cell trait (HbAS and HbSC) and sickle cell disease (HbSS) were 17.5% and 0.5%, respectively [25].…”
Section: Discussionmentioning
confidence: 61%
“…A statistical relationship was observed between sickle cell trait and gender (p < 0.05), which seems to be similar to that reported in Ghana with children, where blood group O was the most prevalent (41.4%), followed by blood groups A (29.6%) and B (23.3%), while AB (5.7%) had the lowest frequency. The authors also showed that the prevalence rates of sickle cell trait (HbAS and HbSC) and sickle cell disease (HbSS) were 17.5% and 0.5%, respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 99%